Biosynthesis and metabolic engineering of isoflavonoids in model plants and crops: a review - Wang, Lijun; Li, Chaofeng; Luo, Keming (Frontiers in Plant Science, 2024)
Isoflavonoids, the major secondary metabolites within the flavonoid biosynthetic pathway, play important roles in plant defense and exhibit free radical scavenging properties in mammals. Recent advancements in understanding the synthesis, transport, and regulation of isoflavonoids have identified their biosynthetic pathways as promising targets for metabolic engineering, offering potential benefits such as enhanced plant resistance, improved biomass, and restoration of soil fertility. This review provides an overview of recent breakthroughs in isoflavonoid biosynthesis, encompassing key enzymes in the biosynthetic pathway, transporters influencing their subcellular localization, molecular mechanisms regulating the metabolic pathway (including transcriptional and post-transcriptional regulation, as well as epigenetic modifications). Metabolic engineering strategies aimed at boosting isoflavonoid content in both leguminous and non-leguminous plants. Additionally, we discuss emerging technologies and resources for precise isoflavonoid regulation. This comprehensive review primarily focuses on model plants and crops, offering insights for more effective and sustainable metabolic engineering approaches to enhance nutritional quality and stress tolerance.